Use of Straw and Wood Shavings as Nest Material in Primiparous does - Blumetto, O.; Olivas, Irene; Torres, Antonio G.; Villagrá, Arantxa (2017)
In rabbit production several materials such as hay straw wood shavings or waste wool and cotton are used as nesting materials during parturition In this work straw and wood shavings were studied as potential materials for nest boxes and a choice test was designed for this purpose Two replicates of 30 primiparous does each were carried out Does were housed 10 d before parturition in a double commercial cage so each doe had access to 2 different nest boxes One of the nests was filled with 8 cm of barley straw and the other with 8 cm of wood shavings so the doe could choose which of them she prepared and gave birth in During the 24 h prior to parturition the state of the nest was assessed according to the mixing of the material and the does hair and the preservation of the original material as well as the chosen nest box When the does gave birth the number of live and dead newborn was recorded In the first replicate 87% of the does chose the straw nest box while in the second replicate 93% of the does did so The number of live kits at birth did not differ statistically for straw and wood shavings nests (8 36 +/- 1 74 vs 6 85 +/- 3 44) but litters reared in straw reacted a higher size at weaning (7 98 +/- 1 73 vs 6 29 +/- 3 35 P<0 05) Finally all the nests achieved a good level of mixing between the original material and the hair of the doe and only 5% of the does removed the original material (regardless of whether it was straw or wood shavings) and made the nest only with their hair In conclusion our results suggest that does might have a strong preference for straw rather than wood shavings as nest material